PELAKSANAAN PENANGGUHAN PENAHANAN ATAS PERMOHONAN KELUARGA TERSANGKA ATAU KUASA HUKUMNYA OLEH PENYIDIK POLRI - Umar Mukhtar (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT Implementation of the Suspension of detention of suspects by investigators who dealt with by the Police Samarinda from year to year has decreased, it can be seen from those obtained from registers Police Samarinda. The decrease is due to the hard work of police officers in menangguhan crime, so that people are afraid of making mistakes due to crime or punishment. There are several reasons that caused the suspension of the application letter that the suspect gained Suspension Detention Detention, among others: Suspect will not run away and do not complicate the course of the examination; Guarantee of the family, to attempt Suspension of Detention; Suspect will not cope with his actions again; The suspect has not been convicted; Still undergoing studies in education institutions. Surety is the right suspect before his term ends, whereas the purpose of detention is to give authority to the investigators and prosecutors and judges to hold against those suspected or reasonably suspected to have committed a crime. The purpose of detention is: Keeping in order not to cause concern for the suspect fled .; Keeping the suspect not to damage or destroy evidence; Keeping suspect criminal offense not to repeat again. In the grant application for the suspension of detention, investigators do not just granted suspension of detention, the case investigator will see the weight of the crime have been bdilakukan by the suspect. Considerations an investigator to accept or reject the application for suspension of detention include: Crime of the accused have not disturbing the public; Suspect young age; Still dibangku school or college. The Penolakam surety can also occur if the suspect would be possible: to escape; suspect residence is not fixed; if possible suspect would destroy evidence to obscure the examination both at the level of investigation and other examinations; Not implementing the terms that have been agreed between the investigators to a suspect, for example, must report and others. The obstacles faced by investigators as follows: Suspect did not heed sayarat provisions or conditions in the surety; the identity of the suspect is unclear and there is no surety for accused.